Stochastic thermodynamics of inertial-like Stuart–Landau dimer - Jung-Wan Ryu; Alexandre Lazarescu; Rahul Marathe; Juzar Thingna (New Journal of Physics, 2021)
Stuart–Landau limit-cycle oscillators are a paradigm in the study of coherent and incoherent limit cycles. In this work, we generalize the standard Stuart–Landau dimer model to include effects due to an inertia-like term and noise and study its dynamics and stochastic thermodynamics. In the absence of noise (zero-temperature limit), the dynamics show the emergence of a new bistable phase where coherent and incoherent limit cycles coexist. At finite temperatures, we develop a stochastic thermodynamic framework based on the dynamics of a charged particle in a magnetic field to identify physically meaningful heat and work. The stochastic system no longer exhibits the bistable phase but the thermodynamic observables, such as work, exhibit bistability in the temporally metastable regime. We demonstrate that the inertial-like Stuart–Landau dimer operates like a machine, reliably outputting the most work when the oscillators coherently synchronize and unreliable with minimum work output when the oscillators are incoherent. Overall, our results show the importance of coherent synchronization within the working substance in the operation of a thermal machine.